A Slower Age-Related Decline in Treatment Outcomes After the First Ovarian Stimulation for in vitro Fertilization in Women With Polycystic Ovary Syndrome - Li, Jing; Liu, Xiaocong; Hu, Linli; Zhang, Fuli; Wang, Fang; Kong, Huijuan; Dai, Shanjun; Guo, Yihong (Frontiers in Endocrinology, 2019)
Background: Polycystic ovary syndrome (PCOS) patients have a better ovarian reserve and age-related improvement in endocrine disturbances than non-PCOS patients. The effects of age on in vitro fertilization (IVF) treatment outcomes associated with cumulative live birth rate (CLBR) remain unclear. Objectives: To study the effect of age on CLBR after the first ovarian stimulation in IVF in PCOS patients. Method: This retrospective cohort study included 3,502 PCOS patients and 18,596 patients with tubal factor infertility, who underwent their first IVF cycles and subsequent frozen embryo transfer (ET) attempts. The primary outcome was CLBR associated with a single stimulation cycle and secondary outcomes included the implantation rate, clinical pregnancy rate, live birth rate (LBR), large for gestational age (LGA) rate, small for gestational age (SGA) rate, and preterm birth (PTB) rate of fresh ET cycles. Results: PCOS patients over 40 years had a higher implantation rate (27.8 vs. 15.7%, P < 0.05), clinical pregnancy rate (51.4 vs. 26.1%, P < 0.05), LBR (42.3 vs. 18.2%, P < 0.05), and CLBR (50.0 vs. 21.5%, P < 0.05) than non-PCOS patients over 40 years. These rates were comparable between PCOS patients aged 35 to 40 years and those aged over 40 years (P = 0.263, 0.385, and 0.112, respectively). The changes in the implantation rate, clinical pregnancy rate, and CLBR by age were slower for PCOS patients than for non-PCOS patients (all P < 0.05). Among PCOS patients less than 35 years, BMI was negatively associated with CLBR [aOR: 0.961 (0.939–0.985); P < 0.05]; however, among PCOS patients over 35 years, instead of BMI (P = 0.353), age [aOR: 0.891 (0.803–0.990); P < 0.05] and the number of oocytes retrieved [aOR: 1.093 (1.002–1.078); P < 0.05] were significantly associated with CLBR. No significant differences in LGA, LGA, or PTB were detected between PCOS and non-PCOS patients over 35 years (all P > 0.05). Conclusions: The declines in treatment outcomes with age are slower for PCOS patients than for non-PCOS patients. For patients over 40 years, PCOS patients have reproductive advantages over non-PCOS patients. In contrast to younger PCOS patients (<35 years), older PCOS patients (≥35 years) may benefit less from taking time to lose weight before IVF treatment, and the immediate initiation of assisted reproductive treatment is essential.